THE PARAMETERS OF MULTILINGUAL LEGAL COMMUNICATION IN A GLOBALIZED WORLD - SANDRINI, Peter (Comparative Legilinguistics, 2009)
In law a tendency towards a tighter global embedding of national legislation can be observed. A few historical notes on the evolving of national legal systems will be the basis for the identification of the parameters of international legal communication and the factors influencing legal translation. An attempt at defining legal translation from the viewpoint of LSP-communication leads to a comprehensive overview of the key parameters for legal translation.